A practical method for incorporation of Fe (III) in Titania matrix for photocatalytic applications. (9th April 2021) - Khalid, Awais; Ahmad, Pervaiz; Alharth, Abdulrahman I; Muhammad, Saleh; Khandaker, Mayeen Uddin; Faruque, Mohammad Rashed Iqbal; Din, Israf Ud; Alotaibi, Mshari A
Abstract: The unprecedented catalytic role of Iron (III) nitrate nonahydrate (Fe (NO3 )3 ·9H2 O) has been explored in a top-down technique for the synthesis and Iron (III) doping of Titanium dioxide nanoparticles (TiO2 -NPs). In the experimental procedure, the chosen 1:1 ratio of Fe (NO3 )3 ·9H2 O and TiO2 bulk powder is allowed to work hydrothermally in top-down synthesis and Fe-doping of (TiO2 ) nanoparticles. Field emission scanning electron microscopy (FESEM) shows the particle structure or morphology of the Fe-doped TiO2 -NPs. Raman and x-ray photoelectron spectroscopy (XPS) is used to study the composition and iron-content at the surface of the synthesized nanoparticles. X-ray diffraction (XRD) pattern has several peaks for α -Fe2 O3 corresponds to Iron doping in the synthesized nanoparticles of (TiO2 ). The current technique provides a practical method for maximum yield and high quality of Fe-doped TiO2 nanoparticles for its potential photovoltaic and photocatalytic applications in modern technologies.